LIMITATIONS OF THE US WRITING CENTER MODEL IN RUSSIA - Irina B. Korotkina (Moscow Polytechnic University, 2016)
Since 2016, the rapid spread of writing centers in Russian universities tends to become a trend. In a few months, their number increased from three to eleven, and the process might soon involve most federal and research universities. Most centers follow the US model of a writing center with its hand-off approach to tutoring. Experts from the USA also show increased interest in the process, providing help in consulting future directors. However attractive the adoption of a ready-to-use and efficient model may seem, it is limited by the social, cultural and academic differences between the USA and RF. These differences involve the interests of many agents, who may oppose innovation due to understandable reasons. If this becomes the case, establishing academic writing in the Russian system of education may fail with fewer opportunities to recover in the future. The paper presents the comparative analysis of the US model's efficiency in Russia and the USA based on the seven sets of parameters introduced by Russian economist Oleg Sukharev. The analysis is a part of research carried out by the author for the Russian Presidential Academy of National Economy and Public Administration.